BREAKING UP VOCABULARY: AN INVESTIGATION OF VOCABULARY BOUNDARIES AMONG HOSPITALITY STUDENTS - Andi Rizki Fauzi (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Effective communication skills, particularly English proficiency, are crucial for hospitality students to excel in the global industry. However, existing literature reveals gaps in understanding the vocabulary limitations faced by these students and the underlying factors hindering their progress. This qualitative study aimed to explore the roots of vocabulary limitations among hospitality students through in-depth interviews. The method involved conducting semi-structured interviews with 32 hospitality students to gain insights into their experiences and perspectives. The findings revealed significant obstacles in pronunciation due to differences in sound systems, appropriate use of vocabulary in formal and informal contexts, grasping nuanced meanings, and constructing grammatically correct sentences. Factors such as lack of confidence, difficulties in remembering vocabulary, fluctuating motivation levels, and access to adequate learning resources further exacerbated these limitations. The study underscores the need for tailored interventions, including contextualized vocabulary learning, explicit instruction on usage and sentence construction, effective memory strategies, fostering supportive learning environments, and nurturing intrinsic motivation. By addressing these multifaceted challenges through targeted pedagogical approaches, hospitality educators can better equip students with the linguistic competencies essential for effective communication and professional success in the global hospitality industry.